Stakeholders’ perspectives to improve the delivering of sexual education for adolescents: A systematic review - Yulia Yunara; Ferry Efendi; Makhfudli Makhfudli (Journal of Holistic Nursing Science, 2023)
The number of reports of poor reproductive and sexual health in adolescents is enormous. Sexual education is very critical for adolescent health. Sexual education has shown more effective results when implemented in collaboration with adolescents. Lack of educational resources, issues considered taboo and cultural boundaries, and lack of trust in maintaining confidentiality cause ambiguity and misconceptions about sexual education. Implementing sexual education involves many parties, so this study aimed to analyze the stakeholders' perspectives on sexual education delivery for adolescents. This systemic review was conducted to find relevant articles in Scopus, CINAHL, Science Direct, and ProQuest databases—the research guideline using The PRISMA checklist. The eligibility criteria and The JBI Checklist were prepared as a guide in measuring article quality. In the final review, twelve articles were included. The articles mentioned parents, adolescents, teachers, and other stakeholders' perspectives. Parents' perspectives have who is responsible for educating adolescents, taboo and lack of communication skills between parent-child, contents of sexual education, and delayed sexual education. Adolescents' perspectives, such as sources and ideal versions of sexual education. Teachers' perspectives include people who should be responsible and skill-based teachers. Meanwhile, other stakeholders' perspectives have school-based, religious challenges, partnerships, and communication strategies with adolescents. This study shows the need for improvement in delivering sexual education. Keywords: Stakeholders; sexual education; skill-based teachers; parents care; communication skills